1966
DOI: 10.1128/jb.92.3.565-574.1966
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Synthesis in Killed Bacteria: Lethality of 2′,3′-Dideoxyadenosine

Abstract: Philadelphia), MEEK1 JANSEN, AND SEYMOUR S. COHEN. Polymer synthesis in killed bacteria: lethality of 2',3'-dideoxyadenosine. J. Bacteriol. 92:565-574. 1966.-We studied the metabolic capabilities of cells that had lost the ability to multiply under a variety of lethal treatments. Cultures of a polyauxotrophic mutant of Escherichia coli strain 15 requiring thymine, arginine, uracil, and adenine for growth were killed to a few per cent survivors by several different methods. These treatments included streptomyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1970
1970
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 6 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…The conversion of ddThd to ddTTP is also negligibly slow in E. coli (Atkinson et al, 1969), but d a d o is converted to ddATP in E. coli at a sufficiently rapid rate to allow irreversible inhibition of cellular DNA synthesis (Doering et al, 1966;Toji and Cohen, 1969). This observation raises the possibility that one of the other three ddNs might show more pronounced effects on cells or viruses than those demonstrated by ddThd.…”
Section: Herpes Simplex Virus Type I (Hsv-i) Dna Polymerase Ismentioning
confidence: 99%
“…The conversion of ddThd to ddTTP is also negligibly slow in E. coli (Atkinson et al, 1969), but d a d o is converted to ddATP in E. coli at a sufficiently rapid rate to allow irreversible inhibition of cellular DNA synthesis (Doering et al, 1966;Toji and Cohen, 1969). This observation raises the possibility that one of the other three ddNs might show more pronounced effects on cells or viruses than those demonstrated by ddThd.…”
Section: Herpes Simplex Virus Type I (Hsv-i) Dna Polymerase Ismentioning
confidence: 99%
“…The thymidine triphosphate analog 2/,3'-deoxythymidine triphosphate can be used as a substrate by DNA polymerase I of Escherichia coli and incorporated into growing DNA chains in vitro, whereupon the chains terminate because of the lack of the 3'-hydroxyl group necessary for chain continuation (Atkinson et al, 1969). The nucleoside analog 2',3'-dideoxyadenosine irreversibly inhibits DNA synthesis in E. coli (Doering et al, 1966). In the present study an attempt has been made to utilize the chain-terminating function of 2/,3/-dideoxythymidine (ddT)* 1 *in mammalian cells to ascertain its possible value for analysis of replication in complex systems.…”
mentioning
confidence: 99%
“…The compound had been tested because the absence of a 3'-hydroxyl group indicated that the derived nucleotide might terminate deoxyribonucleic acid (DNA) chains. Indeed, the metabolic lesion observed in E. coli was a relatively specific irreversible inhibition of DNA synthesis (3), a result suggesting the validity of the proposed mechanism of toxicity. More recently, we showed that the triphosphate of this dideoxynucleoside does in fact terminate polydeoxynucleotide chains in vitro when a purified DNA polymerase derived from E. coli is used (16).…”
mentioning
confidence: 73%
“…The lethality of 2',3'-dideoxyadenosine to several strains of Escherichia coli was demonstrated in 1966 (3). The compound had been tested because the absence of a 3'-hydroxyl group indicated that the derived nucleotide might terminate deoxyribonucleic acid (DNA) chains.…”
mentioning
confidence: 99%